PERANAN BADAN KEPEGAWAIAN DAERAH DALAM PELAKSANAAN REKRUTMEN PEJABAT STRUKTURAL ( SUATU STUDIDI KANTOR BADAN KEPEGAWAIAN DAERAHKABUPATEN HALMAHERA SELATAN) - Faeda, Christofel; Rumapea, Patar; Pombengi, Jericho (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : The purpose of this study was to describe the role of the Regional EmploymentBoard in the implementation of recruitment Scope of Structural Officials in SouthHalmahera District Government. To explain Factors (Internal and External) thatmenpengaruhi Regional Employment Agency in peleksanaan recruitment of Civil Servants(PNS) in structural positions within the Government of South Halmahera.The method used is descriptive qualitative approach which describe answer theproblem of the role of the Regional Employment Board in the implementation of recruitment,where the collected data is processed and analyzed descriptively qualitative. The datacollection techniques done using observation, namely through direct observation in the fieldon the real conditions that occur and Interview namely through direct interviews withrespondents, informants or sources.Operationalization of recruitment normatively regulated by Government RegulationNo. 13 of 2002 on Appointment of Civil Servants (PNS) in structural positions, implementedbased on the principle of professionalism in accordance with kopentensi, perestasiemployment ladder rank set for the job, as well as objective conditions other regardless ofgender, ethnicity, race, religion and class.Based recruitment system structural position in South Halmahera Districtmenyisahkan various problems that can affect the performance and program implementationof development of personnel resources in the future. These conditions resulted in employeemotivation is less motivated to achieve organizational effectiveness. So as to apply thedevelopment of personnel resources, it is expected to achieve maximum effectiveness of work.Keywords : Role of Regional Personnel Agency, Recruitment StructurePENDAHULUAN